Practical theory of a social enterprise (Economic and Political Thought, 2015)
The aim of the article is to locate the issue of a social enterprise in thetheory on how companies operate, with particular emphasis on the theory ofa konfirma [a blend ‘con-firm’, coined of ‘consumer’ and ‘firm’], as well as topresent a summary of the results of empirical research into social enterpriseswith a modified concept of the author’s theory of a konfirma.The starting point for this paper is the issue of humanization of the economictheory and empirical economic research methodology. A category ofa social enterprise in the economy has been distinguished and its functions,classification and legislative attempts to regulate it have been presented.A social enterprise has been located in the theories of the firm that arediscussed in contemporary literature. The theory of a konfirma is the mainpart of the theory of the firm identified with a social enterprise. The authorhas modified his theory of a konfirma for the need of including it in the categoryof a social enterprise. To verify the theoretical assumptions, they havebeen confronted with the results of empirical research into social enterprises.